Pengaruh Profitabilitas dan Cash Holding terhadap Nilai Perusahaan - Rahmaniar; Fitrian Rizky (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
The purpose of this study is to examine the effect of profitability and cash holding, either partially or jointly, on firm value in the construction of companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis method in this study uses multiple linear regression to predict the effect of the independent variables. The population in this study is the construction of the Indonesia Stock Exchange company building in 2017-2021. The results showed that profitability and cash holding did not affect the firm value together. Profitability does not affect the value of the company, which means the company or company shares remain the same as the company's asset value to the profit ratio. This shows that high profits do not lead to an increase in firm value. Cash storage does not affect the value of the company, this shows that companies that have small or large cash balances do not affect the increase in company value. This shows that investors do not see the company's cash holdings in their investments. Investors believe that the company's cash holdings are very vulnerable to being used by company executives.